Stability Indicating Assay for the Determination of Bilastine in Bulk Drug and Method Development Validation by RP-HPLC Using Analytical Quality by Design Approaches - Nayak, Anjali; Maria Danish Alwin, R; Sangeetha, G; Sowmya, C Y; Reddy, Yashwanth V; Dang, Raman (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Regulatory organizations have acknowledged the need for systematic rules for understanding development as a result of the large increase in concerns and criticism regarding the quality and pharmaceutical products. Bilastine is a second generation antihistamine medication. Generally, it is used for treatment of allergic rhino conjunctivitis and urticaria (hives). Objectives The current study outlines the methodical design and validation of a reversed-phase high-performance liquid chromatographic method for the estimation of Bilastine in bulk drugs using AQbD approach. Materials and Methods Using Box Behnken design, the critical method parameters were methodically optimized. Risk estimation matrix was performed and Critical Analytical Attributes, Critical Method Attributes were correlated to identify risk factors of method development. A reverse phase column in isocratic elution mode with mobile phase NaH2PO4 buffer and methanol of different ratio and flow rate 1 mL/min was set for RP-HPLC method development. Results Chromatographic separation was accomplished on INTERSIL C8 column. The optimized and predicted data from JMP PRO 14 software consist of mobile phase 0.1N NaH2PO4 (60%): Methanol (40%), pumped at a flow rate of 1 mL/min gave the higher desirability function of 77%. LOD and LOQ are, respectively, 0.005 mcg/mL and 0.016 mcg/ mL. The Rt of Bilastine was discovered to be 1.894 min. The created method was approved and validated in accordance with ICH Q2 (R1) recommendations. Conclusion The chosen models were determined to be significant with p <0.05. The validation parameter findings were within the permitted range. Forcefully testing the drug’s stability under various stress situations revealed considerable degradation in the presence of heat.
Keywords: AQbD; Bilastine; Analytical target profile; Critical method attributes; Design of experiments; RP-HPLC; Validation